Strategi Pemberdayaan UMKM Melalui Pendampingan Legalitas, Promosi Digital Dan Inovasi Produk Desa Macanan, Kec. Jogorogo, Kab. Ngawi - Hammam Baihaqi, Ahmad; Ria Angelina, Salma; Putri Septiana, Eka Salsa; Sari, Nofita; Ayunda Soepratno, Natalia Putri; Nur Khamalia, Novi Aghata; Istiqomah, Nurul; Rosyidi, Hamim (Institut Agama Islam Negeri (IAIN) Kudus, 2025)
Formation of Community in Strengthening National Character Based on Religious Moderation for Students in Kudus Regency. This study examines the empowerment strategy for Micro, Small, and Medium Enterprises (MSMEs) in Macanan Village through a participatory approach conducted by UIN Sunan Ample Surabaya Community Service Program students. Using the Asset-Based Community Development (ABCD) method, this study aims to increase the capacity of MSMEs with a focus on strengthening legality, marketing digitalization, and product innovation. The findings indicate that MSMEs face various challenges, including limited access to business legality and low digital literacy. Programs such as registering MSME locations on Google Maps, creating a Business Identification Number (NIB), creating business labels, training on social media optimization, and product innovation have successfully increased business visibility. In addition, these interventions also strengthened social networks and built MSMEs' self-confidence. This study concludes that empowerment strategies based on local potential not only contribute to economic growth but also to positive social change in the community. Recommendations for program sustainability include continued efforts in mentoring and training, as well as the integration of digital technology.